Consecutive envenomation of two men bitten by the same coral snake (Micrurus corallinus). (1st February 2020) - Bucaretchi, Fábio; Borrasca-Fernandes, Carla F; De Capitani, Eduardo M; Hyslop, Stephen
Abstract: Objective: To report two patients who developed systemic neurotoxicity after consecutive bites by the same coral snake. Case report: Two previously healthy men (32-year-old and 34-year-old) found a coral snake in a woodpile while collecting wood for a barbecue. During the barbecue, both men became drunk and "played" with the snake, believing that they were handling a false coral snake, and were bitten within a few minutes of each other. Both patients were admitted to a referral tertiary care hospital (175 km from where the bites occurred) 16 hours and 19 hours postbite; both showed similar features of envenomation: palpebral ptosis, muscle weakness, dysphagia, and generalized myalgia. No fang marks or local pain were detected in either case. The patients were successfully treated with Brazilian coral snake antivenom (Fab´2 ) and discharged one-day postadmission, with improvement of myasthenia, but still showing palpebral ptosis. The offending snake was identified as a 42-cm-long Micrurus corallinus . During follow-up, both patients reported a transitory loss of taste that lasted approximately 3–4 weeks postbite. Conclusion: Consecutive bites by the same coral snake may cause systemic neurotoxicity (acute myasthenia) in more than one person, as well as transitory loss of taste, an underreported complication of snakebites.